2014
DOI: 10.1039/c4cp01251h
|View full text |Cite
|
Sign up to set email alerts
|

Built-in potential shift and Schottky-barrier narrowing in organic solar cells with UV-sensitive electron transport layers

Abstract: The performance of organic solar cells incorporating solution-processed titanium suboxide (TiOx) as electron-collecting layers can be improved by UV illumination. We study the mechanism of this improvement using electrical measurements and electroabsorption spectroscopy. We propose a model in which UV illumination modifies the effective work function of the oxide layer through a significant increase in its free electron density. This leads to a dramatic improvement in device power conversion efficiency through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The device shows characteristics similar to those of the NIR-emitting devices, such as subbandgap turn-on at 2.2 V (Figure 4 b) and bias-independent emission spectral shape ( Figure S9, Supporting Information). We note that for green LEDs, there are no previous results [ 23,24,39,40 ] COMMUNICATION showing a brightness of >10 000 cd m −2 at an operational voltage of below 3 V achieved by solution-processed polymer or quantum dot LEDs and even vacuum-deposited small-molecule LEDs. A maximum luminance of 20 000 cd m −2 was attained under a driving voltage of as low as 2.8 V. The high brightness achieved at the low voltage can be attributed to small energy losses from carrier injection and high mobility ambipolar carrier transport.…”
Section: Doi: 101002/adma201405217mentioning
confidence: 69%
See 2 more Smart Citations
“…The device shows characteristics similar to those of the NIR-emitting devices, such as subbandgap turn-on at 2.2 V (Figure 4 b) and bias-independent emission spectral shape ( Figure S9, Supporting Information). We note that for green LEDs, there are no previous results [ 23,24,39,40 ] COMMUNICATION showing a brightness of >10 000 cd m −2 at an operational voltage of below 3 V achieved by solution-processed polymer or quantum dot LEDs and even vacuum-deposited small-molecule LEDs. A maximum luminance of 20 000 cd m −2 was attained under a driving voltage of as low as 2.8 V. The high brightness achieved at the low voltage can be attributed to small energy losses from carrier injection and high mobility ambipolar carrier transport.…”
Section: Doi: 101002/adma201405217mentioning
confidence: 69%
“…All layers, with the exception of the MoO x /Au electrode, were deposited from solutions. MoO x /Au bilayers [ 24 ] and ITO with PEImodifi ed ZnO [ 25 ] were selected as the top and bottom electrodes, respectively because of their ohmic carrier injection properties.Figure 2 a shows the EL spectra of the NIR device at various bias voltages. The wide bandgap ZnO nanocrystals were employed as electron-transporting and hole-blocking layers because of the combination of high electron mobility, excellent optical transparency, and a deep valence-band energy level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have made efforts on the construction of a band diagram, based on indirect evidences, such as transient photocurrent [80] and surface potential characterization [85]. Furthermore electroabsorption spectroscopy [97][98][99] has proven as a powerful approach to study the internal electrical field, enabling to directly characterize the field of device in working condition and observe any occurring interfacial barrier modulations [100]. Li et al [10]found that there is a shift of the built-in potential during the device scanning, as shown in Figure 15.…”
Section: Energy Band Bendingmentioning
confidence: 99%
“…EA measurements have been also carried out on organic solar cells to estimate the internal field . The detailed EA experiment has been described elsewhere in literature . In short, an electric‐field modulation, i.e., a superposition of DC and AC voltages, is applied to the device and the relative change in intensity of the reflective probe light, Δ R , is monitored using a silicon detector connected with a lock‐in amplifier.…”
Section: Resultsmentioning
confidence: 99%